A Hadith-Based Love Curriculum in Islamic Education: An Initiative by Indonesia’s Ministry of Religious Affairs - Malik, Masriwaty; Alwi, Zulfahmi; Ilyas, Abustani; Ahmad, La Ode Ismail; Fatmal, Abd. Bashir (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2025)
This study examines the concept of the “Love-based Curriculum” initiated by the Ministry of Religious Affairs of the Republic of Indonesia through the perspective of the prophetic hadiths of the Prophet Muhammad (PBUH). The research focuses on identifying, classifying, and analyzing hadiths that represent the values of love for God (ḥablum minallāh), love for fellow human beings (ḥablum minannās), love for the environment, and love for the homeland. Employing a qualitative approach through a library-based study, this research applies the method of takhrīj al-ḥadīth, followed by sanad and matan criticism to assess the authenticity of the hadiths utilized. This study is conducted to address the existing gap in the development of Islamic education curricula that explicitly draw upon prophetic traditions as primary sources of educational values. The findings reveal that out of 54 identified hadith, the majority are classified as ṣaḥīḥ (authentic) and are appropriate to serve as normative foundations for formulating a value-based curriculum centered on love. These traditions demonstrate a strong correlation with the values of tolerance, empathy, ecological responsibility, and national spirit. The results underscore the urgency of integrating prophetic teachings into the design of an Islamic education curriculum that is more holistic, transformative, and humanistic. A hadith-based Love Curriculum holds substantial potential in shaping a learning ecosystem that not only fosters intellectual excellence but also cultivates moral integrity, strengthens social harmony, and promotes the development of a robust national character.